Expert System To Diagnose The Feasibility Of Drinking Water For Consumption Using Certainty Factor Method In Pdam Tirta Sari Kota Binjai - Niko Ramot Saragi; Arnes Sembiring; Nurhayati (CV. AFDIFAL MAJU BERKAH, 2022)
Drinking water is water that has been processed or without processing that meets health requirements and can be drunk directly. Meanwhile, to find out the water is fit for consumption or not. It is difficult to distinguish what causes errors that lead to problems that occur such as health problems. Such as metal content must be safe for consumption. It takes a system that can be used as an information provider to determine the quality of drinking water suitable for consumption which is managed by PDAM Tirta Sari, Binjai City. An expert system using the certainty factor method in diagnosing the feasibility of drinking water for consumption. Drinking water in determining whether or not water is feasible and helps provide valid information about the feasibility of drinking water for consumption to customers.